PENERAPAN METODE CASE BASED REASONING PADA PEMILIHAN RESEP MAKANAN BERDASARKAN BAHAN - Wahyu Chandra (Teknosia, 2022)
Cooking is an activity carried out by a person by processing food ingredients through the process of applying heat with a specific purpose. In cooking, there are slight differences in the amount of ingredients and seasonings and how they are processed, so a recipe is needed to be used as a reference in cooking. Recipes are measurements used to process food ingredients that have been tested for accuracy. SMK Negeri 3 Bengkulu is one of the Vocational High Schools in Bengkulu City. In the culinary department, students who want to cook still use recipe books (manuals). The main problem in this research is how to assist students in finding information about recipes so that we need a software that can be used in the selection of recipes using the Case Based Reasoning method and Web applications to find recipes that match the food ingredients owned by the user. From the results of the tests carried out the Case Based Reasoning method can be used as a solution in the use of applications to determine the recipe for this food ingredient. In its application, this method can provide a percentage of the level of similarity in searching for a recipe. So that users, especially students of SMKN 3 Bengkulu City, especially in the culinary department, can make this application as a solution for cooking a food recipe with existing ingredients. Based on the system testing carried out, it can be concluded that this application is in accordance with the design and can provide convenience for users to search